2013
DOI: 10.1007/s11785-013-0340-4
|View full text |Cite
|
Sign up to set email alerts
|

Norm Estimates for Weighted Composition Operators on Spaces of Holomorphic Functions

Abstract: This paper shows that the boundedness of a weighted composition operator on the Hardy-Hilbert space on the disc or half-plane implies its boundedness on a class of related spaces, including weighted Bergman spaces. The methods used involve the study of lower-triangular and causal operators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
(30 reference statements)
0
29
0
Order By: Relevance
“…There is a unitary mapping The following is a straightforward Corollary of [4,Thm. 3.2], given that the operator…”
Section: The Next Results Identifies Invertible Weighted Composition Omentioning
confidence: 99%
“…There is a unitary mapping The following is a straightforward Corollary of [4,Thm. 3.2], given that the operator…”
Section: The Next Results Identifies Invertible Weighted Composition Omentioning
confidence: 99%
“…We begin with the following result, which is essentially due to Kacnelson [13], see also [11,Theorem 2.1]. For completeness, we provide a proof.…”
Section: Multiplier Inclusionsmentioning
confidence: 94%
“…In particular, they have found the expression for the norm of composition operators for these spaces and shown that the composition operators must never be compact in this context. Some further results concerning so-called Zen spaces (a generalisation of weighted Bergman spaces) and weighted composition operators have been obtained in [3] and we aim to extend it in this article.…”
Section: Introductionmentioning
confidence: 93%